Factors Associated with Work Fatigue among Firefighters and Rescue Personnel in Jambi City, 2025 - Anggita Basauli; Wilia Novita Eka Rini; Ashar Nuzulul Putra; Budi Aswin Sanrus (PubHealth Jurnal Kesehatan Masyarakat, 2026)
Background: Work fatigue is a commonly reported feeling of tiredness, characterized by decreased activity and motivation, which can affect physical condition and reduce workers’ ability to perform optimally. According to data from the International Labour Organization (ILO), approximately 32% of workers worldwide experience work fatigue Work fatigue is influenced by both internal and external factors. This study aims to examine the relationship between age, nutritional status, years of service, physical workload, and stress and work fatigue among personnel at the Fire and Rescue Department of Jambi City. Method: This study used a quantitative method with an analytical observational approach and a cross-sectional design. The population in this study consisted of 180 personnel. The minimum sample size required to represent the study population was 78 respondents. Sampling was carried out using probability sampling with the Proportionate Stratified Random Sampling technique. This study uses chi-square test. Results: The results of the chi square statistical test showed that there was a relationship between age (p-value = 0,005), length of service (p-value = 0,000), and physical workload (p-value = 0,000) with work fatigue. There was no relationship between nutritional status (p-value = 0,978) and stress (p-value = 0,154) with work fatigue. Conclusion: There is a relationship between age, length of service, and physical workload with work fatigue among personnel at the Fire Fighter and Rescue Department of Jambi City. Then there is no relationship between nutritional status and stress with work fatigue among personnel at the Fire Fighter and Rescue Department of Jambi City.